Narrative as a Factor of the Spirit of the Poetry in the Poetry of Nasirjon Jorayev - Kurbanbayev Ilhombek Aminbayevich (Peerian Journals Publishing, 2022)
Nasirjon Jorayev, one of the talented poets who strives to expand the boundaries of Uzbek verse during the period of national independence, has an individual style of expression, originality of narration, denial of conflicts in emotions and consciousness and deep philosophy that unites these two points and leads to socio-philosophical generalization. tendency is noticeable. Therefore, in the example of the poet's work, the common illumination of the harmony of the narrative nature and the spirit of the poem determines the relevance of the topic.
Keywords: Narrative; poetic spirit; aesthetic principles; poetic idea